VARIATION OF THE SUPERFICIAL HARDNESS OF THOSE RADIAL ROLLERS OF TRANSPORTERS YACOBI - Leyva de la Cruz, Benigno (Nexo Revista Científica, 2014)
One of the medullary problems that has affected the productivity of the companies in general, is the deterioration of the pieces of their technological equipment for waste. In such a sense, the study of the behavior of the superficial hardness of these components during its useful life is of vital importance, to be able to recommend an efficient structure, as for the material and treatment to select. In this work was carried out a study on the variation of the superficial hardness that experiences the radial rollers of transporters yacobi during their period of exploitation. The influence was determined that have about the hardness the combined effect of the temperature, the force, the number of revolutions, and the cooling régime in the steel AISI 1045, laminate and temperate. The determination the superficial hardness of 12 rollers was made before and after the setting in exploitation with an instrument to measure hardness portable model 316 with range of mensuration of 20 - 65 HRC and appreciation 1,5 points, assuring the condition of normality for a level of trust of 95%. The results obtained indicate that the hardness of the rollers is before 47,5 HRC and 41,67 HRC and after the exploitation respectively. Also, the analysis of made variance refers that significant difference exists before among the values of the superficial hardness and after the setting in exploitation, what indicated the necessity to carry out a meticulous analysis of the causes that are causing this variation to improve the quality of the process. DOI: http://dx.doi.org/10.5377/nexo.v27i01.1439